Synthesis and evaluation of novel lipidated neuromedin U analogs with increased stability and effects on food intake. (17th December 2014) - Dalbøge, Louise S.; Pedersen, Søren L.; van Witteloostuijn, Søren B.; Rasmussen, Jakob E.; Rigbolt, Kristoffer T. G.; Jensen, Knud J.; Holst, Birgitte; Vrang, Niels; Jelsing, Jacob
<x xml:space="preserve">Abstract</x> Neuromedin U (NMU) is a 25 amino acid peptide expressed and secreted in the brain and gastrointestinal tract. Data have shown that peripheral administration of human NMU decreases food intake and body weight and improves glucose tolerance in mice, suggesting that NMU receptors constitute a possible anti‐diabetic and anti‐obesity drug target. However, the clinical use of native NMU is hampered by a poor pharmacokinetic profile. In the current study, we report in vitro and in vivo data from a series of novel lipidated NMU analogs. In vitro plasma stability studies of native NMU were performed to investigate the proteolytic stability and cleavage sites using LC–MS. Native NMU was found to be rapidly cleaved at the C‐terminus between Arg24 and Asn25, followed by cleavage between Arg16 and Gly17. Lipidated NMU analogs were generated using solid‐phase peptide synthesis, and in vitro potency was investigated using a human embryonic kidney 293‐based inositol phosphate accumulation assay. All lipidated analogs had preserved in vitro activity on both NMU receptors with potency improving as the lipidation site was moved away from the receptor‐interacting C‐terminal octapeptide segment. In vivo efficacy was assessed in lean mice as reduction in food intake after acute subcutaneous administration of 1, 0.3, 0.1, and 0.03 µmol/kg. These lipidated NMU analogs prolonged the anorectic effect of NMU in a dose‐dependent manner. This was likely an effect of improved pharmacokinetic properties because of improved vitro plasma stability. Accordingly, the data demonstrate that lipidated NMU analogs may represent drug candidates for the treatment of obesity. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.